Kontribusi Objek Wisata Pantai Firdaus dan Pengaruhnya Terhadap Pendapatan Masyarakat Desa Kema II Kceamatan Kema Kabupaten Minahasa Utara - Mottoh, Rommy J.R (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: One source of income for the villagers of North Minahasa Regency Kema II is the presence of coastal attractions of Firdaus. Tourist attraction the beach more or less has provided valuable contribution to the economy of a village community Kema II. The results of this research describe how the influence through Beach Tourism object contributions Firdaus Kema II against earnings of society. An research result of explain that there is a significant contribution of the coastal attractions of Firdaus Kema II against earnings villagers Kema II. People tend to experience increased revenues due to the visit of the domestic and foreign tourists in the beach of Firdaus Keywords : Contribution Of Coastal Attractions Of Firdaus, Earnings Of Society, Village Kema II